Operating Performance Analysis and Goods Service Tax Implementation in Malaysia - Sitraselvi Chandren; Ayoib Che Ahmad; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2018)
The implementation of Goods Service Tax (GST) in business processes requires firm to revise their business policies and practices particularly on price setting and cash flow operation that may possibly influence the operating performance. Thus, the purpose of this study is to investigate the impact of GST on operating performance. This study investigated 265 Malaysian listed firms operating performance (profitability: sales growth SG, profit after tax-PAT, return on asset (ROA), liquidity: operating cash flows (OCF) and current ratio CR) from year 2014 (before), 2015 (during) and 2016 (after) GST implementation period using the paired t-test. The SG have shown decreased during the GST implementation period, subsequently improved after the GST implementation period. The CR has exhibited a remarkable improvement during and after GST implementation period. The SG and CR results validate the firms are able to maintain the operating performance even with minimal reduction is witnessed for PAT, ROA and OCF during and after GST implementation. This study contributes to all stakeholders that GST do not necessarily influence the firms negatively, but allows the management of the firm in making effective decision for the operating business processes and supply chain for sustaining the firm value. In sum, this study finds that GST is a business friendly tax system for firms with effective operating performance to support the country economic development.